Бурозубки (Insectivora, Sorex) Анадырской низменности - Охотина, М.В. (Вестник зоологии, 1973)
Seven species of Insectivora (Sorex) are established to inhabit the Anadyr lowland: Sorex caecutiens L a x m., S. arcticus K e r r., S. daphaenodon T h o m., S. minutissimus Z i m m., S. sir AI le n, S. cinereus K e r r. and S. centralis T h o m. The latter is found in the given region first. Three biotopes are described and the number of Insectivora (Sorex) inhabiting them is given. An evident decrease in the number and the impoverishment of the species composition of Insectivora (Sorex) are observed in the Anadyr lowland in the north-eastern direction as the forests are substituted by the tundra.